The Pandemic Blenny, Coralliozetus clausus, a new species of tube blenny endemic to Isla del Coco, Costa Rica (Teleostei: Chaenopsidae) - Hastings, Philip A. (Zootaxa, 2021)
Coralliozetus clausus, a new species of chaenopsid blenny, endemic to Isla del Coco, Costa Rica, is described. This small species, not exceeding 15 mm SL, is a short-bodied member of the genus along with Coralliozetus cardonae (Caribbean), Coralliozetus angelicus, and Coralliozetus springeri (both eastern Pacific). It differs from its closest relative, C. springeri, known from mainland waters from Costa Rica to Ecuador, in having a single tiny supraorbital cirrus and dark dots on the operculum and branchiostegal membrane of males while C. springeri has paired supraorbital cirri (one of which is substantial in size) and no dots on the operculum. Although two other species of Coralliozetus have been reported from Isla del Coco, this appears to be only member of the genus present on the island. It is the second chaenopsid endemic to Isla del Coco and brings the number of cryptobenthic fishes endemic to Isla del Coco to twelve.